Experience forming of healthy way of life of senior pupils in native pedagogic (second half of XX century) - Iermakova T.S (Kharkov National Pedagogical University, 2010)
Generalized and analysed experience of forming healthy way of life of senior pupils in native pedagogic of the second half of XX century. Basic directions of forming healthy way of life of senior pupils are exposed in a probed period. The forms of educational activity, forms of organization of educational day, forms of education are described. The features of activity of groups and sections are certain as forms of out-of-school work of schoolchildren. The basic methods of forming healthy way of life of senior pupils are certain. Facilities of forming healthy way of life of studying young people are specified: facilities of evident agitation and medium of communication.